The practicality and relevance of peace in an EFL teacher training program: Applications and implications. Issue 1 (2nd January 2019) - Vasilopoulos, Gene; Romero, Gloria; Farzi, Reza; Shekarian, Mariana; Fleming, Douglas
ABSTRACT: This study examines the practicality and relevance of positive peace (Galtung, 1964) in English as a foreign language (EFL) teacher training. It focuses on a collaborative three-month study abroad program, funded by the Chinese Scholarship Council, for EFL teachers from rural communities in western China to participate in an intensive professional development program hosted at a large Canadian university. Beginning with the premise that the teaching and learning of Global English is not apolitical, and that the power imbalance between Center based institutions and remote Periphery communities should not be ignored, we consider how the concept, and practice, of positive peace can counter English linguistic and cultural hegemony. In Summer 2016, thirty-five teachers from western China attended the program; thirteen agreed to participate in interviews and focus groups for research purposes. Thematic analysis was used to first code the data for prominent themes with subsequent rounds of interpretive coding to uncover the presence of latent concepts expressed through counter-discourse, such as peace. Through this analytical approach, the data revealed that the visiting teachers (1) disagreed with host instructors on the utility of specific pedagogic approaches; (2) prioritized their own local curriculum; and (3) hoped to teach their hosts about China, as well as learn about EFL pedagogy and Canadian culture. By reading the data through the framework of positive peace, the counter-discourse between visiting teachers and host instructors/researcher can be viewed as sites of peace-building where expertise can be contested, professional identities reasserted, and once silenced voices heard.